1998
DOI: 10.1002/chin.199850289
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Novel Acetogenins from the Leaves of Dasymaschalon sootepense.

Abstract: The hexane extract from the leaves of Dasymaschalon sootepense Craib ( Annonaceae) showed strong cytotoxic activity against the L1210 tumor cell line. Activity-directed fractionation of the extract by column chromatography on silica gel and high-pressure liquid chromatography led to the isolation of the acetogenins 1 ± 4 as the main active principles. The structures of the two novel structures named sootepensin A (1) and sootepensin B (2) were elucidated by spectroscopic analysis ( UV, EI-and ESI-MS, 1D-and 2D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Members of the genus such as Dasymaschalon lomentaceum are promising source of biodiesel fuel (Winayanuwattikun et al 2008). Few of the phytochemical studies on this genus revealed the presence of cytotoxic alkaloids from Dasymaschalon blumei (Chanakul et al 2011), Dasymaschalon rostratum (Li-Dong et al 2001), Dasymaschalon sootpense (Sinz, Rudolf, Ludger, et al 1998;Sinz, Rudolf, Thomas, et al 1998) and Dasymashcalon trichophorum (Xiao-Lei et al 2013); acetogenis from D. sootpense (Sinz, Rudolf, Ludger, et al 1998;Sinz, Rudolf, Thomas, et al 1998 Research, 2014Vol. 28, No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the genus such as Dasymaschalon lomentaceum are promising source of biodiesel fuel (Winayanuwattikun et al 2008). Few of the phytochemical studies on this genus revealed the presence of cytotoxic alkaloids from Dasymaschalon blumei (Chanakul et al 2011), Dasymaschalon rostratum (Li-Dong et al 2001), Dasymaschalon sootpense (Sinz, Rudolf, Ludger, et al 1998;Sinz, Rudolf, Thomas, et al 1998) and Dasymashcalon trichophorum (Xiao-Lei et al 2013); acetogenis from D. sootpense (Sinz, Rudolf, Ludger, et al 1998;Sinz, Rudolf, Thomas, et al 1998 Research, 2014Vol. 28, No.…”
Section: Introductionmentioning
confidence: 99%
“…28, No. 3, 156-163, http://dx.doi.org/10.1080/14786419.2013 and D. rostratum (Li-Dong et al 2001); cytotoxic xanthone from D. sootpense (Reutrakul et al 2001); as well as flavonol glycosides from D. sootpense (Sinz, Rudolf, Ludger, et al 1998;Sinz, Rudolf, Thomas, et al 1998). In addition, antimycobacterial, antiplasmodial and cytotoxic cycloartane-type triterpenoids and flavanone were isolated from Dasymaschalon dasymaschalum (Prawat et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Twelve species are found in Thailand [1][2]. These plants have been reported to contain various types of secondary metabolites, including, alkaloids [3a-b,4], acetogenins [5], xanthones [6] and flavonol glycosides [7]. Previous research on the phytochemical constituents of D. blumei [3a], D. sootepense [3b], D. dasymaschalum [1] and D. trichophorum [8] indicated that some of these were cytotoxic to cancer cell lines, including mouse lymphoid neoplasma (P-388), human epidermoid carcinoma of the mouth (KB), human colon cancer (Col-2), human lung cancer (Lu-1), rat glioma (ASK) and human breast cancer (MCF-7), without affecting the viability of the noncancerous human embryonic kidney cell line (Hek 293).…”
mentioning
confidence: 99%
“…A flavone, dasytrichone and a collection of aristolactam alkaloids were isolated from D. trichophorum [2][3]. Flavonol glycosides [4], acetogenins [5], aporphine alkaloids [6] and a xanthone, sootepenseone [7] were isolated from leaves of D. sootepense. Flavones, alkaloids and a cyclic peptide were isolated from Desmos rostrata (basionym: D. rostratum) [8][9][10].…”
mentioning
confidence: 99%
“…D. sootepense Craib is a small tree growing up to 10-m in height and found in the Northern part of Thailand. Phytochemical studies of the hexane and methanol extracts of the leaves of D. sootepense were reported as part of our on-going search for cytotoxic compounds from plants [4][5][6][7]. A caged xanthone, sootepenseone, with potent cytotoxic activity against KB and MCF-7 cell lines was also isolated from the ethyl acetate extract of the leaves of D. sootepense [7].…”
mentioning
confidence: 99%